Harm to others from alcohol: the role of socio-cultural variables - Florenzano, Ramón; Huepe, Gabriela; Barr, Michelle (Acta Bioethica, 2016)
This paper describes the changes in alcohol research, from a traditional individual focus on individual bodily and mental effects, to a broader focus on harm to others. This shift has coincided with broader sequential definitions of the progression from normal through harmful alcohol dependence, both in the specialized epidemiological and also in the newer classificatory systems (DSM 5 and CIE 11 draft). After presenting updated global, regional and chilean data, an international collaborative Project (Alcohol Harm to Others, ATOH) is described, with the participating institutions: the local study and the chilean components of the research team, the conceptual framework of harm to others (families, children, women; neighbors, friends, co-workers; society at large). Ethical aspects and institutional approval are presented and the principal results outlined: socio-demographic data (with special focus on the role of gender, socio-economic level and religiosity/spirituality). The data is presented for the chilean sample, with examples from other participating countries. The complexity of the link between alcohol harm to others and religious and spiritual factors is studied comparing data from several of the participating countries, and the impact upon vulnerable populations, especially women and children. The discussion reviews some of the confounding and intervening factors that could influence the results. The conclusion about prevention and policy development closes the paper.